Personal Branding of Pelalawan Regent H ZUKRI as a Politician Serving The People - Hasbullah Tanjung; Belli Nasution; Muchid (Kemudi, 2024)
The level of public trust in the political elite is decreasing day by day, so that only a few politicians are able to maintain their image in society, the Regent of Pelalawan H Zukri being one of them. H Zukri's success in the 2009, 2014 and 2019 legislative elections, and continued with his victory in the 2020 Pelalawan Regional Election is an indicator that H Zukri is a figure who truly protects society, including the poor. This of course cannot be separated from H Zukri's personal branding, as a politician who is able to be a beacon of hope for poor people. This research uses a qualitative approach using the concept of personal branding by Montoya & Vandehey. Before becoming a politician, H Zukri was known as a humanist and often paid attention to the poor, and he gave this attention consistently according to his authority, whether direct or policy. It is hoped that this research will provide inspiration and benefits for politicians who want to shape their image and also the results of this research can help H Zukri to evaluate the process of forming his image. The level of public trust in the political elite is decreasing day by day, so that only a few politicians are able to maintain their image in society, the Regent of Pelalawan H Zukri being one of them. H Zukri's success in the 2009, 2014 and 2019 legislative elections, and continued with his victory in the 2020 Pelalawan Regional Election is an indicator that H Zukri is a figure who truly protects society, including the poor. This of course cannot be separated from H Zukri's personal branding, as a politician who is able to be a beacon of hope for poor people. This research uses a qualitative approach using the concept of personal branding by Montoya & Vandehey. Before becoming a politician, H Zukri was known as a humanist and often paid attention to the poor, and he gave this attention consistently according to his authority, whether direct or policy. It is hoped that this research will provide inspiration and benefits for politicians who want to shape their image and also the results of this research can help H Zukri to evaluate the process of forming his image.